The tragic and the ecstatic : the musical revolution of Wagner's Tristan und Isolde - Chafe, Eric Thomas, 1946- (Oxford University Press, 2005)
Covers the philosophical and literary underpinnings of Wagner's and Schopenhauer's story. This work explores Schopenhauer's metaphysics and Gottfried van Strassburg's Tristan poem. It turns to the events in the opera, providing tonal and harmonic analyses to reinforce its interpretation of the drama. It also creates an account of Ristan.